Analisis Pengendalian Persediaan Bahan Baku Serbuk Warna dengan Pendekatan Periodic Review Joint Replenishment untuk Sistem Persediaan Stokastik di PT XYZ - Ahmad Fahmi Izzuddin; Dwi Sukma Donoriyanto (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
PT XYZ is a manufacturing company engaged in the manufacture of extruded aluminum profile products. The problem experienced by PT XYZ is that the company often orders several types of color powder raw materials separately even though they come from the same supplier. This causes more frequent orders to be made. The company also sometimes experiences shortages and excess stock of color powder raw materials which can cause swelling of the company's inven-tory costs. The purpose of this study is to determine the optimal inventory control of color pow-der raw materials to minimize the company's total inventory costs. This research was conducted using a probabilistic model approach with the periodic review joint replenishment method. This method is carried out with a periodic review (p) model, ordering raw materials will be carried out in combination every certain time interval. The calculation results obtained the minimum total inventory cost is with the Periodic Review Joint Replenishment method of Rp 19.519.552.589,- compared to the company method of Rp 19.670.799.095,-. Thus, a savings of Rp 151.246.506 is obtained, or a savings percentage of 0.8%. Forecasting for the period November 2023 - October 2024, the value of the order time interval is obtained every 15 working days with the inven-tory level of each raw material is for white powder of 22.336 kg, brown powder of 12.413 kg, black powder of 8.290 kg, and milk white powder of 1.882 kg with a total inventory cost of color powder raw materials of Rp 19.559.415.435.